Phonetic and grammatical information in the German-Russian dictionaries of the 18th century - L.I. Akhmetsagirova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
Within the Russian lexicography, one of the important, but still unsolved tasks is the creation of a scientific history of German-Russian lexicography. There are not so many special works devoted to the analysis of the results of its activities in the historical perspective. Still unexplored remains the problem of the phonetic and grammatical information in the dictionaries of the 18th century. This paper presents a comparative analysis of nine general bilingual and multilingual dictionaries published in Russia in this period of time as separate books, which included a German language as a target one. The aim of this work is to study the facts of presentation and elaboration of the phonetic and grammatical information, dynamics of the introduction, ways of presentation, forms and content of this information given in relation to German and Russian words. We have revealed that the dynamics of the presentation and the scope of elaboration of the phonetic and grammatical information in the dictionaries are different. The results of the analysis of the phonetic and grammatical information allows us to give a more complete and detailed assessment of the development and achievements of the German-Russian lexicography in the 18th century.